The Role and Future Prospects of Microorganisms in Fermented Food Production - Jin, Yuxin (Transactions on Environment, Energy and Earth Sciences, 2024)
Microbes have been used in the production of fermented food for a long time. Through the use of microorganisms, food fermentation can not only improve the flavor of food, but also improve the nutritional value of food. With the progress of modern fermentation technology, the microbial cultivation technology is becoming more and more mature, and more and more fermented or semi-fermented products such as artificial meat, bean paste, yogurt and liquor appear on the market. In the perspective of the whole food industry, microorganisms in the processing of food production fermented food in the future also has a huge development space, using genetic engineering, molecular biology and other frontier biotechnology microbial research, explore the mechanism of microbial fermentation raw materials and the connection between microorganisms, so as to realize in the process of fermentation to microorganisms more scientific and reasonable regulation, and improve the quality of fermented food. This paper makes a detailed summary of the role of microorganisms in food processing and the application status of microorganisms, and provides suggestions on the future development prospects of microorganisms, and provides reference for the development of microbial fermentation technology in the food field.